슬롯 다이 코팅 균일도 평가를 위한 실용적인 중량계측 기반 유량 측정 방법 - 윤경택; 배정현; 최영만 (한국정밀공학회지, 2023)
Slot-die coating is a method of coating a wide layer of thin film on a substrate. It has the advantages of large-area coating with high reproducibility and uniform thickness. For this reason, it has been widely applied in various industrialmanufacturing fields. To secure higher coating uniformity under various coating conditions, estimating and controlling the flow rate of the coating solution discharged to the substrate is crucial. In this study, a practical gravimetric flow rate measurement method for slot-die coating uniformity evaluation has been introduced. The gravimetric method is a technique for accurately and quickly estimating the flow rate through the mass change over time using a precision weighing balance. We analyzed the measurement principle and errors caused by fluid mechanics such as hydrodynamic force or capillary force. The dynamic properties based on fluid viscosity were also evaluated for flow rates from 5 to 50 μL/s. The repeatability of the fabricated measurement system was ~1.5 μL/s. Finally, it was confirmed that the settling time for highviscosity fluid could be advanced by 56.4% through multi-step feedforward control.
Keywords: Slot-die coating; Gravimetric method; Flow meter; Coating uniformity; 슬롯 다이 코팅; 중량계측법; 유량계; 코팅 균일도